Increasing Brand Awareness through Event Marketing on Social Entrepreneurship - Evanthi , Ayundha; Azhar, Ratih Mukti (Future Science, 2023)
Due to its potential to lessen social problems and enhance people's wellbeing, social entrepreneurship is a developing phenomena that is currently gaining a lot of public attention. Social entrepreneurship events may offer venues crucial opportunities to improve the event's purpose and experiences. (1) Examine event management and social entrepreneurship, paying particular attention to the connections, dimensions, and context-specific roles that each play. (2) Establish the relationship between social entrepreneurship and event management so that it can be incorporated into a later theory. This study uses VOSviewer to map how event management may be applied in social entrepreneurship from a number of prior articles using bibliometric analysis.